EVALUATION OF 67Ga CROSS SECTIONS USING EXIFON CODE FOR MEDICAL APPLICATIONS - Usman, Ahmed Rufai; Ahmad, A. A. (FUDMA JOURNAL OF SCIENCES, 2022)
Radioisotopes play very important roles in nuclear medicine for imaging and therapeutic applications. In the present studies, model calculation of excitation function for production of 67Ga radioisotope was performed using the EXIFON code, a nuclear reaction cross sections theoretical model code, for the reaction 65Cu(Î±, 2n)67Ga. The work was performed in the incident alpha energy range of 0 - 40 MeV. Similarly, the Q-value software (interface) was used for the calculation of reaction threshold and Q-value energies of the reaction of interest and were respectively found to be 14.97 MeV and -14.10 MeV. The calculated excitation function has a peak value of 1025 mb around 25 MeV incident energy. The results from the EXIFON code were compared with the experimentally measured cross sections data retrieved from IAEA database, the EXFOR database, as well as the theoretical data from Talys code via its library, the TENDL-2019. Our results partially agree with the theoretical data from Talys code (via the TENDL-2019 library) within the investigated energy region. The results however overestimated the measured (experimental) data and only agree in shape of the excitation function. The present work does not consider the effect of shell structure during the execution of the EXIFON model code. This work could be of importance to the developers and users of nuclear reaction model codes for new developments and enhancements of the existing codes, as well as to serve as a rough guide for experimentalists during production of radioisotopes for nuclear medicine applications